Analysis of elementary school teacher education students' perceptions of potentials and challenges of implementing the deep learning approach - Meilani Tirta Sari; Mazda Leva Okta Safitri; Nurdin Kamil; Bunda Harini; Ilham Arya Susanto; Ari Saputra; A. Aswasulasikin (Universitas Muhammadiyah Malang, 2026)
Background-Twenty-first-century education necessitates the development of critical, creative, and problem-solving capabilities, for which the Deep Learning Approach, grounded in the principles of mindfulness, meaningfulness, and joyfulness, is considered a relevant solution. As prospective teachers, the perceptions of Elementary School Teacher Education students regarding this approach are vital for its successful implementation. However, previous research on these perceptions has been general and has not specifically examined the context of the Elementary School Curriculum holistically. Objective-This study aims to analyze the perceptions of Elementary School Teacher Education students concerning the potential and challenges of utilizing the Deep Learning Approach in Elementary Schools. Method-A quantitative method with a survey design was employed. The sample consisted of 86 Elementary School Teacher Education students from Sriwijaya University, selected purposively based on the criteria of having completed the 5th semester and having participated in relevant training. Data were collected using a Likert scale questionnaire and analyzed using descriptive statistics. Results-The results indicate that students perceive the approach as having significant potential to enhance intrinsic motivation, 21st-century skills, collaborative learning environments, and student autonomy. Conversely, they also recognize complex challenges, such as the need for longer time allocation, limitations in technological infrastructure, difficulties in transforming teachers' mindsets, the complexity of the assessment system, and the need for massive and continuous teacher training. Conclusion-The conclusion suggests that while promising, the implementation of the Deep Learning Approach in Elementary Schools requires a systematic strategy encompassing curriculum adjustments, enhanced infrastructural support, and ongoing professional development for teachers to realize its potential optimally.